Time management from an Islamic perspective: a qualitative study - Islam, Rafikul; Wahra, Ali Mohamed; Ahmed , Selim (2014)
Time is a precious commodity and extremely important amanah from Allah (swt). Proper utilization of time leads to success in this mundane world and eternal bliss in the hereafter. Since time is limited in our life, we must utilize it in the best possible manner so that we can attain eternal success. Most of the existing guidelines on time management are developed by Western scholars some of which may not be consistent with teachings of Islam. The main purpose of the present research is to develop some guidelines on time management from Islamic perspective. In this study, a qualitative interview method was applied to know the Islamic time management practices. Research data were collected through face to face interviews at IIUM. In this study, mainly three important issues were considered regarding the Muslims perceptions on time management from Islamic perspectives: (1) personal views on time management from Islamic perspective; (2) managing time in the daily life; and (3) identifying the time wasters based on experiences. These three key issues were analyzed based on Interpretative Phenomenological Analysis (IPA) process.